2020
DOI: 10.1111/ffe.13245
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study on fracture behaviour of three‐flawed sandstone specimens after high‐temperature treatments

Abstract: The crack coalescence of rocks significantly affects the stability of rock engineering, and extensive studies have been performed on preflawed rock specimens without thermal treatment. However, the fracturing behaviour of preflawed specimens after thermal treatment has not been investigated comprehensively. In this study, three‐flawed sandstone specimens with different flaw inclinations after high‐temperature treatments were tested under uniaxial compression. Photographic, acoustic emission and digital image c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 68 publications
0
6
0
Order By: Relevance
“…To investigate the crack coalescence mechanism of pre-flawed rocks after high-temperature treatments, uniaxial compression tests on three-flawed sandstone specimens heated to high temperatures were performed by Huang et al 97 During the testing, the photographic, AE, and DIC techniques were used to investigate the crack initiation, propagation, and coalescence behaviors. Huang et al 98 further investigated the effects of thermal shock on the strength and cracking behavior of preflawed granite specimens under uniaxial compression. The experimental results demonstrated that strain concentration bands were first emanated from the flaw tips and developed with a continuous increase of external stress, followed by the propagation and coalescence of macrocracks.…”
Section: Crack Initiation and Growth In Flawed Rocks Due To Temperature Treatmentsmentioning
confidence: 99%
“…To investigate the crack coalescence mechanism of pre-flawed rocks after high-temperature treatments, uniaxial compression tests on three-flawed sandstone specimens heated to high temperatures were performed by Huang et al 97 During the testing, the photographic, AE, and DIC techniques were used to investigate the crack initiation, propagation, and coalescence behaviors. Huang et al 98 further investigated the effects of thermal shock on the strength and cracking behavior of preflawed granite specimens under uniaxial compression. The experimental results demonstrated that strain concentration bands were first emanated from the flaw tips and developed with a continuous increase of external stress, followed by the propagation and coalescence of macrocracks.…”
Section: Crack Initiation and Growth In Flawed Rocks Due To Temperature Treatmentsmentioning
confidence: 99%
“…In confined pore spaces, damage can occur due to ice pressure that breaks the skeleton of the rock particles. However, the volume expansion theory has been questioned by other scholars as rocks under natural conditions are more likely to have connected pores [7]. The hydrostatic pressure theory was proposed in the study of concrete freeze-thaw damage due to the connectivity of pores within the rock.…”
Section: Related Workmentioning
confidence: 99%
“…However, the difficulty and large cost of testing for the fracture toughness of rocks at real-time high temperatures have forced researchers to study the fracture characteristics by testing heat-treated rocks that cooled to room temperature. [24][25][26] However, the effect of thermal damage caused by temperature on the fracture toughness at room temperature is quite different from that at high temperatures. The research on heat-treated rocks cannot fully reflect the mechanical behaviors of rocks in practical engineering.…”
Section: Introductionmentioning
confidence: 99%